Modeling transient vibration-sound generation processes (Моделювання, керування та інформаційні технології, 2020)
In this paper, a problem of sound generation of two-blade rotor sinusoidal shape during helicopter landing is solved. Near and far sound field characteristics have been calculated. A comparative analysis of obtained numerical results with results for Mach number 0.2